There's more to money! GET A LIFE - Abd Razak, Dzulkifli (2007)
THE transition into the Chinese New Year went well, what with a wellknown feng shui master predicting good fortune ahead, based on the reading of the stars. A number of geomancers and astrologers also claimed that the New Year is indeed a year of plenty. This is seemingly confirmed by some of the economic data announced by the government earlier on. Notably, Malaysia's total trade exceeded the RM1.069 trillion mark last year for the first time. This placed the country in the league of top exporting nations like Taiwan, South Korea, Japan, Germany and the Netherlands. This quantum leap is un precedented in the history of the nation, representing a 10.5 per cent growth over that in 2005.